Kids in the Middle: The Micro Politics of Special Education - Strax, Marshall; Strax, Carol; Cooper, Bruce S. (Rowman & Littlefield Publishers, 2012)
Kids in the Middle: The Micro-Politics of Special Education takes the reader on a fascinating journey through special education in the past, present, and future. On this journey, the micro-politics of special education are seen through the eyes and experiences of children with disabilities, their parents and advocates, adult educators, and school administrators. Supplementing these perspectives to develop an understanding of special education that goes beyond its administrative and political aspects, such as the Individuals with Disabilities Education Act (IDEA), are scholars with expertise in special education law, administration, severe and profound disabilities, ethics, finance, teaching, and disability rights. Together, these voices explain the micro-political issues that affect how children with disabilities are educated. Kids in the Middle promotes a new model of special education to help transform special education. Instead of perpetuating a system grounded in the concepts of promises, privilege, and power, this book considers how to build a system based on caring, compassion, and the common good, a system that will elevate the status of special education children who are lost in the middle.